The Effectiveness of the Think Pair Share Learning Model on Student Learning Activities in Science Class IV SDN 067250 Medan Deli - Syarifah Ainun; Mastari Ramadhani (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2023)
The research design used was True-Experimental Design research with a population of all fourth grade students at SDN 067250 Medan Deli totaling 46 people, namely 25 students in the experimental class and 21 people in the control class. The data collection technique used was a performance test that had been previously tested using a rater reliability test and a content validation test. While testing the hypothesis using the t test (independent sample t-test). Based on the results of the research conducted, it is known that the predata data for the experimental and control classes are normally distributed and homogeneous. The value of t-count predata is smaller than t-table (-0.30956 <1.684), meaning that Ho is accepted. Ho is accepted, meaning that the experimental and control groups have the same variance at the time of pre-data. The posttest results show that the data for both classes are normally distributed and homogeneous. The posttest t-count value is greater than the t-table price (2.072 > 1.684), meaning that Ha is accepted. Ha is accepted, meaning that Think Pair Share is more effective when compared to conventional methods for science learning outcomes for fourth grade students at SDN 067250 Medan Deli. The effectiveness of the Think Pair Share model is expected to be a consideration for fourth grade teachers at SDN 067250 Medan Deli to apply the Think Pair Share model to science learning with other aspects or materials. The use of the Think Pair Share model is expected to be an effective science learning model.